Microbiological quality control of non-sterile compounded medicines prepared in a Portuguese hospital centre. Issue 4 (19th January 2016) - Palmeira-de-Oliveira, R; Luís, C; Gaspar, C; Bogas, E; Morgado, M; Guardado, M; Castelo Branco, M; Fonseca, M O; Palmeira-de-Oliveira, A
Abstract : Objectives: This work aimed to evaluate the quality of non-sterile formulations compounded at Centro Hospitalar Cova da Beira (Covilhã, Portugal) immediately after preparation and up to the defined 'beyond-use date'. Methods: Microbiological quality control tests were performed in accordance with monograph 5.1.4 of the European Pharmacopoeia 8.0. Samples of compounded products were collected from January to December 2014 after preparation and were analysed immediately and reanalysed after storage under the established conditions, for each preparation. Results: In the test period, 392 preparations were analysed, corresponding to 24 different formulations (8 intermediate preparations, 11 oral solutions/suspensions and 5 topical preparations). All preparations were in accordance with the pharmacopoeia specifications immediately after preparation. However, for the formulations 'prednisolone oral solution (5 mg/mL)' and 'nitroglycerine and cinchocaine ointment (0.25%/0.5%)', the microbial counts of some batches exceeded the defined limits after storage up to the beyond-use date. Conclusions: These results show that the compounding practices implemented at this pharmacy department are able to ensure the microbiological quality of compounded products. This microbiological quality control methodology also allowed identification of the need to replace formulations shown not to be stable throughout the storage period. On the basis of these results, a monthly routine of microbiological control of a random sample of compounded medicines was established in order to ensure their quality and safety for use.